Polyinosinic: polycytidylic acid induced inflammation enhances while lipopolysaccharide diminishes alloimmunity to platelet transfusion in mice - Tran, Johnson Q.; Muench, Marcus O.; Gaillard, Betty; Darst, Orsolya; Tomayko, Mary M.; Jackman, Rachael P. (Frontiers in Immunology, 2023)
Alloimmune responses against platelet antigens, which dominantly target the major histocompatibility complex (MHC), can cause adverse reactions to subsequent platelet transfusions, platelet refractoriness, or rejection of future transplants. Platelet transfusion recipients include individuals experiencing severe bacterial or viral infections, and how their underlying health modulates platelet alloimmunity is not well understood. This study investigated the effect of underlying inflammation on platelet alloimmunization by modelling viral-like inflammation with polyinosinic-polycytidylic acid (poly(I:C)) or gram-negative bacterial infection with lipopolysaccharide (LPS), hypothesizing that underlying inflammation enhances alloimmunization. Mice were pretreated with poly(I:C), LPS, or nothing, then transfused with non-leukoreduced or leukoreduced platelets. Alloantibodies and allogeneic MHC-specific B cell (allo-B cell) responses were evaluated two weeks later. Rare populations of allo-B cells were identified using MHC tetramers. Relative to platelet transfusion alone, prior exposure to poly(I:C) increased the alloantibody response to allogeneic platelet transfusion whereas prior exposure to LPS diminished responses. Prior exposure to poly(I:C) had equivalent, if not moderately diminished, allo-B cell responses relative to platelet transfusion alone and exhibited more robust allo-B cell memory development. Conversely, prior exposure to LPS resulted in diminished allo-B cell frequency, activation, antigen experience, and germinal center formation and altered memory B cell responses. In conclusion, not all inflammatory environments enhance bystander responses and prior inflammation mediated by LPS on gram-negative bacteria may in fact curtail platelet alloimmunization.